Development of a Molecularly Imprinted Polymer-Based Sensor for the Electrochemical Determination of Triacetone Triperoxide (TATP) - Samuel Kassahun Mamo; Jose Gonzalez-Rodriguez (Sensors, 2014)
The explosive triacetone triperoxide (TATP), which can be prepared from commercially readily available reagents following an easy synthetic procedure, is one of the most common components of improvised explosive devices (IEDs). Molecularly-imprinted polymer (MIP) electrochemical sensors have proved useful for the determination of different compounds in different matrices with the required sensitivity and selectivity. In this work, a highly sensitive and selective molecularly imprinted polymer with electrochemical capabilities for the determination of TATP has been developed. The molecular imprinting has been performed via electropolymerisation onto a glassy carbon electrode surface by cyclic voltammetry from a solution of pyrrole functional monomer, TATP template and LiClO4. Differential Pulse Voltammetry of TATP, with LiClO4 as supporting electrolyte, was performed in a potential range of −2.0 V to +1.0 V (vs. Ag/AgCl). Three-factor two-level factorial design was used to optimise the monomer concentration at 0.1 mol∙L−1, template concentration at 100 mmol∙L−1 and the number of cyclic voltammetry scan cycles to 10. The molecularly imprinted polymer-modified glassy carbon electrode demonstrated good performance at low concentrations for a linear range of 82–44,300 µg∙L−1 and a correlation coefficient of r2 = 0.996. The limits of detection (LoD) and quantification (LoQ) achieved were 26.9 μg∙L−1 and 81.6 μg∙L−1, respectively. The sensor demonstrated very good repeatability with precision values (n = 6, expressed as %RSD) of 1.098% and 0.55% for 1108 and 2216 µg∙L−1, respectively. It also proved selective for TATP in the presence of other explosive substances such as PETN, RDX, HMX, and TNT.